SURVEI KEJADIAN DEPRESI PADA PASIEN STROKE DI DESA SIDODADI KECAMATAN LAWEYAN SURAKARTA - Kristanto, Budi; Yulianti, Tunjung Sri; Wibowo, Devianti Kristianingrum (KOSALA : Jurnal Ilmu Kesehatan, 2015)
Background. Depression is a major mental health problem because of the depressed productivity will decline and bad for the community, state and nation. In the clinical experience is often found that in patients with stroke in addition to the symptoms of neurological disorders (such as paralysis or locomotor muscles of the face and so on), also found the mental-emotional disorders such as depression, apathy, euphoria even to the mania. Hawari (2004), states that pravelensi depression in stroke patients reach 40% - 60% in the first 6 months after stroke. Based on the survey and initial observations stroke in Sidodadi Pajang Laweyan Surakarta, whose house is adjacent to the researchers, the data can be acquired, some stroke patients show behavioral symptoms of depression.Research purposes. To describe the level of depression in patients with stroke in Sidodadi Pajang Laweyan Surakarta.Methods. This research is a descriptive cross sectional approach. The subjects of this study are patients with stroke men and women in Sidodadi Pajang Laweyan Surakarta number of 20 respondents. Data obtained by direct visits and the using of instruments quesionare Hamilton Rating Scale for Depression (HRS-D). The data obtained and analyzed by univariate analysis using SPSS 16 for Windows.Result. The majority of that number seven respondents (35%) in a state of severe depression, 6 respondents (30%) in a state of depression is very severe, 4 respondents (20%) experienced mild depression, 2 respondents (10%) had moderate depression and only 1 respondent in normal conditions, or no depression. Mean (average) level of depression of the respondents is 19.1 which indicates the level of depression among respondents with at Sidodadi Stroke is a severe depression.Conclusion. From this study it can be concluded that the majority of respondents with a stroke depressed.Keywords: Stroke, depression